Pentingnya Manajemen Strategi Dalam Meningkatkan Kualitas Pendidikan - Apriansyah, Andika; Salsabila, Fara Naia; Ana, Indah Fitri; Pebrianti, Sylvina; Nasution, Inom (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The quality of education is a key factor in building quality and competitive human resources. To achieve high quality education, effective strategic management is needed. Strategic management includes planning, organizing, leading and controlling processes aimed at achieving organizational goals. In the educational context, strategic management plays an important role in determining the direction and priorities for the development of educational institutions, as well as allocating resources optimally to achieve educational goals. This journal examines the importance of implementing strategic management in improving the quality of education. Through literature studies, this journal shows that good strategic management can increase the effectiveness and efficiency of the educational process, improve the quality of graduates, and strengthen the competitiveness of educational institutions. Apart from that, appropriate strategic management can also facilitate the development of relevant curricula, increase the competence of educators, and provide adequate educational facilities and resources.